Testing specific physical performance in male team handball players and the relationship to general tests in team sports - Wagner, H.; Sperl, B.; Bell, J. W.; von Duvillard, S. P. (The Journal of Strength and Conditioning Research, 2019)
Team handball is exemplified by frequent changes in intensities and different complex movements during games, whereas physical performance has often been tested predominantly using standardized general tests. The study aimed (a) to determine the relationship between specific and general physical performance as well as between specific aerobic capacity and agility, and (b) to ascertain the relevance of these tests for strength and conditioning professionals. Seventy-two male indoor court players performed a game-based performance test (GBPT) including team handball-specific techniques, upper-body and lower-body strength tests, a 30-m sprint test, a countermovement jump Abalakov (CMJA) test (with arm swing), and an incremental treadmill-running test. To assess the specific physical performance using the general test performance, we used linear regression calculations. In addition, a principal component factor analysis was calculated. Linear regression analyses revealed a low correlation (R < 0.5) between specific and general aerobic performance, 30-m sprinting time and specific agility in the GBPT, jump height in the CMJA test and jump height in the jump shot, as well as isokinetic shoulder rotation torque and ball velocity in the jump shot. However, a moderate correlation (R > 0.5) was found between specific aerobic performance and specific agility in the GBPT. Principal component factor analysis yielded separate components for specific and general physical performance with a cumulative variance of 69%. The results of this study clearly indicated that general and team handball-specific performance are separate components. Recommendations to strength and conditioning professionals and coaches in team handball were presented.